Establishment and application of quadruple fluorescence quantitative RT-PCR method for the identification of waterfowl astrovirus - Li, Yang; Luo, Juan; Zhang, Fuyou; Shang, Jiajing; Deng, Chunran; Feng, Yingjie; Meng, Ge; Jiang, Wenming; Yu, Xiaohui; Liu, Guanhui; Liu, Hualei (Frontiers in Microbiology, 2024)
Avian astroviruses can infect a wide range of avian species and cause viral diarrhoea, which is widespread, highly pathogenic and has a high incidence rate, causing a certain impact on the healthy development of China's waterfowl aquaculture industry. In order to achieve rapid detection of DAstV-3, DAstV-4, GoAstV-1 and GoAstV-2, a multiplex fluorescent RT-PCR method was developed in this study. DAstV-3, DAstV-4, GoAstV-1 and GoAstV-2 can be detected simultaneously in one reaction tube, which consumes short time and has good specificity. Compared with the routinely used RT-PCR method, the limit of detection by the multiplex RT-PCR lower. Subsequently, 269 clinical samples were tested by this method and the results showed that the positivity rate of DAstV-4 was high, while the positivity rates of DAstV-3, GoAstV-1 and GoAstV-2 were low, and mixed infections existed between DAstV-4 and GoAstV-1 and GoAstV-2.